Behaviour of the T. cruzi blood forms obtained from mice used as biological filters in culture and triatomine - Ribeiro, Rosa Domingues; Belda Neto, Francisco Miguel; Prado Junior, José Clóvis do; Albuquerque, Sérgio de (Revista de Saúde Pública, 1986)
The study of the behaviour of T. cruzi strains in animals as in human beings, runs into great difficulties when the attempt is made to relate the morphology of this parasite to its biological behaviour. The thin forms are able to penetrate vertebrate cells faster than the broad forms. So, faced with the biological complexity of the T. cruzi strains and substrains it was decided to investigate the behaviour of its blood forms obtained from normal mice as biological filters. These mice were endovenously inoculated with blood trypomastigotes from derivated RCL of the T. cruzi RC strain. Forty-eight hours later, the animals went through xenodiagnosis and heart punch in order to sow the blood in Warren's medium. The trypomastigotes became round (spheromastigotes and/or amastigotes) in the stomach of the triatomines and cultures at 28°C. The behaviour of the broad forms has been frequently observed and leads to the conclusion that the biology of the T. cruzi is not only related to the strain, but, sometimes, to the parasite population.